Teaching Informatics in the Kurikulum Merdeka: An exploratory case study at SMPN 12 Bandung - Alya Nurul Hanifah (Himpunan Pengembang Kurikulum Indonesia, 2025)
This study aims to examine the implementation of Informatics teaching within the context of the Kurikulum Merdeka at Junior High School (SMP) Negeri 12 Bandung. This research focuses on three aspects, namely implementing Project-Based Learning (PjBL), developing teaching materials relevant to students' lives, and applying continuous formative assessment. The findings reveal that the PjBL approach significantly increased student engagement and enhanced their basic digital skills, particularly in creating digital presentations and animations. Teachers play a crucial role as learning facilitators, capable of designing responsive learning experiences and adapting materials to students' needs. Despite challenges such as infrastructure limitations and unequal access to technology, adaptive solutions like blended learning and unplugged activities were successfully implemented. This study highlights the need for continuous teacher training in digital pedagogy and strong institutional support to enhance the implementation of the Kurikulum Merdeka. The findings aim to contribute to the development of best practices in contextual Informatics teaching and provide valuable insights for policy development based on the Kurikulum Merdeka. Abstrak Penelitian ini bertujuan untuk mengkaji implementasi pengajaran informatika dalam konteks Kurikulum Merdeka di SMP Negeri 12 Bandung. Fokus penelitian ini mencakup tiga aspek utama, yaitu penerapan Project-Based Learning (PjBL), pengembangan bahan ajar yang relevan dengan kehidupan peserta didik, dan penerapan asesmen formatif berkelanjutan. Temuan menunjukkan bahwa pendekatan PjBL secara signifikan meningkatkan keterlibatan peserta didik dan mengembangkan keterampilan digital dasar mereka, khususnya dalam pembuatan presentasi dan animasi digital. Guru memainkan peran penting sebagai fasilitator pembelajaran yang mampu merancang pengalaman belajar yang responsif dan menyesuaikan materi dengan kebutuhan peserta didik. Meskipun dihadapkan pada tantangan seperti keterbatasan infrastruktur dan ketimpangan akses teknologi, solusi adaptif seperti blended learning dan aktivitas unplugged berhasil diterapkan. Penelitian ini menekankan pentingnya pelatihan guru secara berkelanjutan dalam pedagogi digital serta dukungan kelembagaan yang kuat untuk memperkuat implementasi Kurikulum Merdeka. Temuan ini diharapkan dapat berkontribusi pada pengembangan praktik terbaik dalam pengajaran Informatika yang kontekstual serta memberikan wawasan berharga bagi pengembangan kebijakan berbasis Kurikulum Merdeka. Kata Kunci: Kurikulum Merdeka; pendidikan informatika; praktik pengajaran